Power simulation of a CubeSat: influence of orbit, attitude and thermal control - Santana, Andre L. Rodrigues (2023)
CubeSats must endure the extreme temperature and radiation changes that are a result of the environment in orbit. The power system of CubeSats, which produces the electrical energy required to carry out the activities, is a crucial component. The photovoltaic effect, a phenomenon whose maximum power point decreases as temperature rises while the peak rises with solar radiation intensity rises, is used by the majority of satellites, including CubeSats, to convert solar radiation into electrical energy. High temperatures should be avoided since they decrease the effectiveness of this photovoltaic phenomenon, whereas high solar radiation levels are required to produce more energy. This study evaluates a simulation of a CubeSat 1U with solar panels mounted on all of its faces to examine the impact of orbit, attitude, and temperature management on power generation. The outcomes show that higher performance may be obtained by carefully choosing these factors.